Remittances, Financial Sector Development and Economic Growth in Nepal: A Time-Series ARDL Analysis - Regmi, Krishna Kumar (Butwal Campus Journal, 2025)
This study examines the dynamic relationship between remittance inflows, financial development, and economic growth in Nepal using annual time-series data from 1995 to 2024. It analyzes the long-run and short-run interactions among the variables by observing historical patterns of remittance inflows, financial development indicators, and GDP per capita. Employing the Autoregressive Distributed Lag (ARDL) model, the study finds that remittance inflows have a positive short-run effect on economic growth, whereas financial development shows a negative short-run influence but becomes growth-enhancing with a one-year lag. In the long run, however, both remittance inflows and financial development exhibit a negative and significant impact on GDP per capita, suggesting that their long-term contribution to economic growth remains weak or constrained. The findings highlight the complex nature of Nepal’s remittance-driven economy, where remittances support short-term consumption and liquidity but fail to generate sustained economic growth. The results underscore the need for stronger financial intermediation and productive utilization of remittances to ensure long-term economic gains.